Bearing Capacity Analysis of Pile Foundation in Reservoir Construction - Ningrum, Puspa; Husnah; Saputro, Dimas Andrian (Rumah Jurnal, 2023)
The foundation was an important part of the structure. In foundation design, it was necessary to considered the foundation condition to be built must be able to support the load up to the allowable capacity. To determine a safe foundation requires analysis using several of static methods. This research was conducted to obtain a critical bearing capacity so that it can be used to determine a very safe foundation. In this study, analysis of the bearing capacity of pile foundations was calculate using the method of Briaud et al. (1985), Meyerhof (1956), Decourt (1982), Shioi & Fukui (1982) based on SPT N-value obtained from the field at borehole 1 (BH-01) and borehole 2 (BH-02). Based on the analytical result of the bearing capacity calculation of a pile foundation with a diameter of 0.35m on depth of 24m, The lowest of bearing capacity (critical value) used to determine the number of piles is the method of Briaud et al. (1985) was 90.55 tons at borehole 1 and 87.06 tons at borehole 2. This value was use as a guideline for determining the number of pile foundations used in reservoir construction design.